PENGARUH LAYANAN INFORMASI MELALUI MEDIA VIDEO SHORT MOVIE UNTUK PERSIAPAN SISWA MEMASUKI PERGURUAN TINGGI DI SMAN 11 MUARO JAMBI - Bunga Ezila Febyya. I; Rasimin; Dinny Rahmayanty (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2026)
This study aims to examine the influence of guidance information services delivered through short movie video media on students’ readiness to enter higher education at SMAN 11 Muaro Jambi. The background of the study stems from the lack of students’ motivation and preparedness in seeking information regarding higher education, as well as the limited appeal of traditional media like brochures. In line with technological advancements, short movie videos are considered a more interactive medium that can enhance student engagement. The research employed a quantitative associative approach using correlational methods. The sample consisted of 100 twelfth-grade students selected through purposive sampling. Data were collected through questionnaires and analyzed using simple linear regression. The findings reveal a significant influence of informational services delivered via short movie videos on improving students' readiness in academic, psychological, social, and financial aspects to pursue higher education. These results suggest that visually engaging media can serve as an effective tool to disseminate educational information and enhance students' understanding and interest in continuing their education. The study recommends the broader application of short movie videos within school counseling services to assist students in making more informed and focused educational decisions.